Expressions of Legendre polynomials through Bernoulli polynomials - Tuan, Vu Kim; Tinh, Nguyen Thi (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A formula for expanding Legendre polynomials in Bernoulli polynomials is considered. The relationship is established by using a formula of finite summation, obtained by applying the discrete orthogonal relation of the modified Lommel polynomials.